Cost analysis and barriers to implementing and sustaining an international surgical resident rotation: a retrospective review. Issue 1 (April 2020) - Onuh, Ogechukwu; Fisher, Rebecca; Trinidad, Stephen; Divino, Celia; Marin, Michael; Trejo, Pedro; Khetan, Prerna; Zhang, Linda
Abstract: Background: The overwhelming need and interest in global surgery has led to increasing numbers of international surgery resident rotations. Despite the validity of global surgical education, financial and logistical barriers remain when implementing these international rotations. The Mount Sinai Department of Surgery, New York, USA, established an international resident rotation in 2005. Here, we describe some of the costs and barriers to establishing and maintaining a global surgery rotation with the aim of providing a guideline for academic institutions interested in building an international rotation. Methods: This study is a retrospective review of the international rotation with the Hospital Jose Maria Cabral y Báez (Cabral) in Santiago, Dominican Republic. The exchange programme is an opportunity for two resident doctors from Dominican Republic to join Mount Sinai third year residents in a 1-month surgical rotation. We reviewed data collected from budgets, financial investments, resident and programme director experiences, and formal agreements between the two institutions. Findings: With the Mount Sinai funding, there have been three residents from the Dominican Republic who have completed an exchange rotation at the Mount Sinai Hospital. An optimum international site requires a balanced alliance between the US academic institution and the international site. The Cabral and Mount Sinai collaborative partnership allows residents from both institutions to benefit from the exchange of experiences and surgical practices. Site selection is contingent on: hospital infrastructure (eg, operative variety and volume, faculty oversight); suitable living accommodations that allow personal safety, access to food, running water, electricity, and an internet connection; and overcoming language barriers. Successful implementation requires a time commitment from staff at both institutions. The monthly operational cost of this programme is US$3530, with 37% for visiting resident accommodation, 30% for transport, 20% for visiting resident expenses, and 13% for health and communication expenses. The time required by the US programme director includes an annual trip to the international rotation site and approximately 100 h per year, which includes monthly orientations and debriefings, and research. Finally, this programme requires adherence to Accreditation Council for Graduate Medical Education and Residency Review Committee guidelines. Interpretation: Global academic surgery combines surgery with education, clinical service, research, and advocacy in resource-limited settings. Mitigation of logistical barriers and addressing financial costs allows for successful global academic surgery programmes. Funding: None